Incidence and Risk Factors of Acute Kidney Injury in Critically Ill Patients in Intensive Care Units of Tertiary Care Hospitals (Journal of Fatima Jinnah Medical University, 2024)
Background: Over the last decade, the occurrence of acute kidney injury (AKI) in intensive care units (ICUs) has risen due to heightened severity and improved identification of such cases. The study objectives are to identify the incidence and evaluate the risk factors of acute kidney injury in critically ill patients in tertiary care hospitals.Patients and methods: This cross-sectional study was carried out between July and August 2022 at Pakistan Institute of Medical Sciences and Federal Government Services Hospital, Islamabad Pakistan. The study involved the collection of data from 300 critically ill patients admitted to medical, cardiac, and surgical ICUs. The severity of AKI was evaluated according to Kidney Disease Improving Global Outcomes (KDIGO) staging. Patients’ information regarding history of renal disease in family, comorbidities, kidney functions, measurements of urea and creatinine levels was collected. Subsequently, the analysis was conducted at SPSS v 23.Results: Patients mean age was 60.65 ± 4.87 years. Those who developed AKI post-ICU admission had a mean urea level of 61.64 ± 7.5 mg/dl and creatinine 1.63 ± 0.1mg/dl, which increased to 2.2 ± 0.1mg/dl at the time of diagnosis. Majority cases of AKI were categorized as stage 1 (40%) and stage 2 (60%). Among the patients, 60% (n=180) maintained normal kidney functions, while 40% (n=120) developed AKI during their ICU stay. Notably, 35.7% (n=70) of those who developed AKI were males. A notable association was observed between AKI development and factors such as sepsis, hypovolemia, ischemic heart diseases, age, diabetes mellitus, and hypertension (p-value ≤0.05).Conclusion: The key point of the study highlighted a notable incidence of AKI among ICU-admitted patients. Sepsis and hypovolemia emerged as the primary causative factors leading to the onset of AKI.
Keywords: Acute kidney injury; Critical illness; Hospitals; Intensive care units Risk factors